Objective measures of functional impairment for degenerative diseases of the lumbar spine: a systematic review of the literature - Stienen, Martin N.; Ho, Allen L.; Staartjes, Victor E.; Maldaner, Nicolai; Veeravagu, Anand; Desai, Atman; Gautschi, Oliver P.; Bellut, David; Regli, Luca; Ratliff, John K.; Park, Jon (The spine journal, 2019)
The accurate determination of a patient's functional status is necessary for therapeutic decision-making and to critically appraise treatment efficacy. Current subjective patient-reported outcome measure (PROM)–based assessments have limitations and can be complimented by objective measures of function. To systematically review the literature and provide an overview on the available objective measures of function for patients with degenerative diseases of the lumbar spine. Systematic review of the literature. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Two reviewers independently searched the PubMed, Web of Science, EMBASE, and SCOPUS databases for permutations of the words “objective,” “assessment,” “function,” “lumbar,” and “spine” including articles on human subjects with degenerative diseases of the lumbar spine that reported on objective measures of function, published until September 2018. Risk of bias was not assessed. No funding was received. The authors report no conflicts of interest. Of 2,389 identified articles, 82 were included in the final analysis. There was a significant increase of 0.12 per year in the number of publications dealing with objective measures of function since 1989 (95% CI 0.08–0.16, p<.001). Some publications studied multiple diagnoses and objective measures. The United States was the leading nation in terms of scientific output for objective outcome measures (n=21; 25.6%), followed by Switzerland (n=17; 20.7%), Canada, Germany, and the United Kingdom (each n=6; 7.3%). Our search revealed 21 different types of objective measures, predominantly applied to patients with lumbar spinal stenosis (n=67 publications; 81.7%), chronic/unspecific low back pain (n=28; 34.2%) and lumbar disc herniation (n=22; 26.8%). The Timed-Up-and-Go test was the most frequently applied measure (n=26 publications; 31.7%; cumulative number of reported subjects: 5,181), followed by the Motorized Treadmill Test (n=25 publications; 30.5%, 1,499 subjects) and with each n=9 publications (11.0%) the Five-Repetition Sit-To-Stand test (955 subjects), as well as accelerometry analyses (336 subjects). The reliability and validity of many of the less-applied objective measures was uncertain. There was profound heterogeneity in their application and interpretation of results. Clinical studies on patients with lumbar degenerative diseases increasingly employ objective measures of function, which offer high potential for improving the quality of outcome measurement in patient-care and research. This review provides an overview on available options. Our findings call for an agreement and standardization in terms of test selection, conduction and analysis to facilitate comparison of results across cohorts. CRD42019122622